Non-Gaussian statistics of pencil beam surveys - Amendola, Luca (Arxiv, 1994)
We study the effect of the non-Gaussian clustering of galaxies on the statistics of pencil beam surveys. We find that the higher order moments of the galaxy distribution play an important role in the probability distribution for the power spectrum peaks. Taking into account the observed values for the kurtosis of galaxy distribution we derive the general probability distribution for the power spectrum modes in non-Gaussian models and show that the probability to obtain the 128$\hm$ periodicity found in pencil beam surveys is raised by roughly one order of magnitude. The non-Gaussianity of the galaxy distribution is however still insufficient to explain the reported peak-to-noise ratio of the periodicity, so that extra power on large scales seems required.